EBU'L-HASAN EL-EŞ'ARÎ'NİN HADİS ANLAYIŞI - URAL, CEMAL (Fırat Üniveristesi, 2022)
Hadislerin anlaşılması ve ifade ettikleri epistemolojik değer hadis problemlerinin başında gelen hususlardandır. Eş'arî'nin İslam düşünce tarihinde önemli bir yer tutmuş olması onun fikirlerini önemli hale getirmektedir. Ayrıca kitaplarında yoğun bir şekilde hadis kullanması dikkatleri çekmektedir. Kelâmcı olmakla birlikte hadisler hakkındaki yorumları ve onları itikâdi konularda delil olarak kullanması hadisleri anlama ve epistemolojik değerlerini belirleme açısından önem arz etmektedir. Eserlerinin çoğunun günümüze ulaşmaması, bazen birbiriyle çelişen ifadeler kullanması ve ona farklı görüşler isnat edilmesi çalışmanın zorlukları arasında zikredilebilir. Konu büyük ölçüde Eş'arî'nin kitapları çerçevesinde ele alınmıştır. Onun kendi eserlerinde zikrettiği görüşler asıl olarak kabul edilmiş ancak gereken yerlerde başkaları tarafından ona atfedilen görüşlere de temas edilmiştir. Kullandığı hadislerin tahrîci, lüzumlu yerlerde de sıhhat değerlendirmeleri yapılmıştır. Hadisle ilgili ıstılahlara verdiği anlamlar tespit edilmeye çalışılmıştır. Eş'arî, düşüncelerini temellendirirken mütevâtir hadislerin yanında haber-i vâhidleri de delil olarak kullanmıştır. Bunları bazen âyetlerle birlikte zikrederken bazen de sadece hadislerle istişhadda bulunmuştur.

Understanding of the hadiths and the epistemological value that they express are among the leading issues of hadith problems. The fact that Ash'ari has an important place in the history of Islamic thought makes his ideas significant. It is also noteworthy that he used hadith intensively in his books. Although he is a theologian, his interpretations of the hadiths and using them as evidence on theological issues are important in terms of understanding the hadiths and determining their epistemological values. The fact that most of his works have not reached the present day, that he sometimes used contradictory statements and that different opinions attributed to him can be mentioned among the difficulties of the study. The study is generally discussed within the scope of Ash'ari's books. In this work, the opinions that he mentioned in his own works were accepted as the main ones, but where necessary, the opinions attributed to him by others were also mentioned. Moreover, the sources of the hadiths he used are pointed out, authenticity evaluations have also been made where necessary. The meanings given by Ash'ari to the terms related to the hadith have been tried to be determined. Ash'ari while substantiating his thoughts, used the isolated tradition as well as the massively transmitted hadiths as evidence. He sometimes mentioned them together with the verses while sometimes provided evidence just with hadiths.
Ebu Al-Hasan Al-Ashari's understanding of hadith
Keywords: Din